Own price elasticities of the demand for sugar-sweetened beverages in Bangladesh - Rumana Huque; Abul Kalam Azad; Nasiruddin Ahmed (BMC, 2024)
Abstract Background Consumption of sugar-sweetened beverages (SSB) is a major global public health problem. Increasing the price of SSBs through taxation is an effective tool to reduce SSB consumption. Price-elasticity estimates are useful in measuring the effect of taxation on consumption. We estimated the own price elasticities of demand for SSBs in Bangladesh, which will inform how SSB taxes could affect behaviour. Methods We used Household Income and Expenditure Survey (HIES) 2016 data, which is a nationally representative dataset at the household level across the country and is conducted using stratified random sampling method. Deaton's method was used to estimate the price elasticities for SSBs in Bangladesh. Results We found that the own price elasticity for SSBs varied between − 0.53% to -1.17% by types of SSBs in Bangladesh. The price elasticity for soft drinks was − 1.17, indicating that if the price of soft drinks increases by 10% via taxes, the quantity consumed of these beverages would reduce by 11.7%. Conclusion This is the first study that estimates the own price elasticities of demand for SSBs in Bangladesh. Our results suggest to raise SSB prices through increased taxation in order to reduce SSB consumption and ensure public health gains in Bangladesh.